Maximizing Rewards Through Work Infrastructure - Gunawan Nainggolan, Hendra; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
This study aims to analyze the influence of Competence and Work Discipline on Rewards, with Work Infrastructure as a moderating variable at PT PLN (Persero) Rantauprapat Customer Service Implementation Unit. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) as the method of analysis. A total of 86 employees participated as respondents in this study. The results show that Competence (coefficient = 0.388; T-statistic = 3.266; P-value = 0.001) and Work Discipline (coefficient = 0.276; T-statistic = 2.307; P-value = 0.011) have a positive and significant effect on Rewards. Work Infrastructure also has a positive and significant effect on Rewards (coefficient = 0.362; T-statistic = 3.274; P-value = 0.001). However, the moderation analysis revealed that the interaction between Competence and Work Infrastructure (coefficient = -0.031; T-statistic = 0.235; P-value = 0.407) and the interaction between Work Discipline and Work Infrastructure (coefficient = 0.112; T-statistic = 0.900; P-value = 0.184) do not have significant effects on Rewards. Therefore, employee rewards are more directly influenced by competence, discipline, and the availability of work infrastructure, rather than by the moderating role of infrastructure.